Novel properties of antimicrobial peptide anoplin - Jindřichová, Barbora; Burketová, Lenka; Novotná, Zuzana (Biochemical and biophysical research communications, 2014)
Antimicrobial decapeptide anoplin was tested for its antifungal activity against plant pathogen Leptosphaeria maculans and protection of Brassica napus plants from disease. To reveal the mode of action of the peptide, a natural form of anoplin amidated on C-terminus (ANP-NH2), and its carboxylated analog (ANP-OH) were used in the study. We demonstrated strong antifungal activity of anoplin in vitro regardless C-terminus modification. In addition we show that both ANP-NH2 and ANP-OH induce expression of defence genes in B. napus and protects plants from L. maculans infection. The results indicate that the amidation of anoplin is not essential for its antifungal and plant defence stimulating activities.
Keywords: Brassica napus; Plant Diseases; Gene Expression Regulation, Plant; Wasp Venoms; kationické antimikrobiální peptidy; Antifungal Agents; amidy; Ascomycota; nemoci rostlin; Amides; Antimicrobial Cationic Peptides; vosí jedy; regulace genové exprese u rostlin; antifungální látky